Women’s Political Empowerment in Iraq After 2003 - Hamzah, Asaad Ghali (مجلة الشرق الأوسط للدراسات القانونية والفقهية, 2024)
The degree of human development in any society is measured by the extent to which women participate in political life, and Iraqi women, together with many third-world countries, have suffered a real crisis concerning women’s participation in the country’s political life, and many factors have been played in reducing the share and size of women’s participation in political life, including the growing role of the military in political life and the militarization of society during the eight-year war and subsequent events that led to the women’s dissociation and reduction of their role. The role was only after women were granted no-election women share in Iraq’s new constitution after 2003. Women’s political participation is not only about obtaining their political rights but also about their political rights in the legitimacy of freely expressing their ideas within the framework of the institutions and groups of society and participating in political decision-making and practice. Therefore, women’s political skills must be expanded by improving educational opportunities, leadership courses, and exchange programs, and removing institutional and legal barriers limiting Iraqi women’s political participation.